Perbedaan Karakteristik Ibu Hamil Normal Dan Ibu Hamil Dengan Hiperemesis Gravidarum - Pratiwi, Vira; M Aryadi Arsyad; Andi Nilawati; Elizabet C Jusuf (Jurnal Bidan Cendrawasih Palu, 2019)
Pregnant women health behavior who undergo the Hyperemesis gravidarum is influenced by several factors, among others, are : the age, education, attitude, knowledge,income, culture, etc. The research aimed at investigating the characteristic difference between the normal pregnant women and women with the hyperemesis gravidarum. This was the observational research with the cross sectional method. Samples were as many as 52 respondents comprising 26 at normal pregnant woman and women and 26 hyperemesis gravidarum women. The samples were taken using the total sampling technique. The sample criteria were : the gestational age of â‰¤ 12 weeksbeing prepared to sign the informed consent issued by Ethic Committee of Faculty of Medicine, Hasanuddin University. Data were obtained from the direct observation through the questionnaire filling of health data, PUQE questionnaire, Perceived Stress Scale Questionnaire. The data analysis used the Chi-Square test and MannWhitney test. The research results indicates that the age characteristic is (P-value = 0.773), education characteristic (P-value = 0.413), occupational characteristics (P-value = 0.482), menstrual pain history characteristic (P-value = 0.781),history characteristic of prehyperemesis gravidarum (P-value = 0,262), history characteristic of hyperemesis gravidarum on family member is (P-value = 0,02), parity characteristic is (P-value = 0,548),contraceptive use history characteristic is (P-value = 1.00 ), stress history characteristic is (P-value = 0.321), body mass index (BMI) characteristic is (P-value = 0.294), upper arm circumference (UAC) characteristic is (P-value = 1.00). There is no characteristic difference of the age, education, occupation, menstrual pain history, hyperemesis history of previous pregnancy, parity, stress history, body mass index, upper arm circumference, nutritional status, and contraceptive use between the normal pregnant women and hyperemesis gravidarum women. Whereas the hyperemesis gravidarum history on the family members indicates the difference.